AB0100 Mtx combined with ctx inhibited il-6 induced jak2-stat3 activation and the induction of p-gp in peripheral blood lymphocytes of rheumatoid arthritis patients. (15th June 2017) - Chen, K; Mu, Y; Qin, K; Zhao, X; Dong, J; Li, X; Gao, C; Wang, C
Abstract : Background: Rheumatoid arthritis (RA) is a systemic autoimmune disease characterized by irreversible joint destruction and disability. At present, the biggest challenge in the field of RA treatment is the emergence of multidrug resistance (MDR) in the application of disease-modifying anti-rheumatic drugs (DMARDs).The Multidrug resistance Related Protein and Multi Drug Resistance protein 1, also called P-glycoprotein can decreases the intracellular concentration of different drugs. Moreover, cytokines play an increasingly important role in the expression regulation mechanisms of P-gp, especially inflammatory cytokines IL-6. Previously, We have indicated that Interleukin-6 up-regulates P-gp in peripheral blood lymphocytes via the JAK2-STAT3 pathway in RA patients. Through more than ten-years' clinical research, we observed that the therapeutic cycle alliance of methotrexate (MTX) and cyclophosphamide (CTX) has had better curative effect and lower rate of adverse reaction in treating RA. And we didn't found the emergence of MDR. How can the therapeutic alliance of MTX and CTX overcome MDR in RA patients? This study will give the answer. Objectives: To Clarify whether the therapeutic alliance of MTX and 4-hydroperoxycyclophosphamide (4-HC) suppress expression and mRNA of P-gp in peripheral blood lymphocytes of RA through JAK2-STAT3 pathway. Methods: RA patients without any DMARDs and biologic therapy (n=15) were enrolled. P-gp expression level was detected by Flow Cytometry. P-gp mRNA of peripheral blood lymphocytes and the intracellular signaling pathway mediating the effects of MTX and 4-HC on IL-6-stimulated JAK2-STAT3 activation was assessed by RT-PCR. Results: Compared with blank control group, IL-6 induced P-gp, JAK2 and STAT3 expression levels increased significantly ( P <0.05). Compared with IL-6 group, P-gp, JAK2 and STAT3 expression levels of 4-HC group and low MTX+4-HC group both decreased ( P <0.05). the expression levels of P-gp, JAK2 and STAT3 in low MTX group, middle MTX group and high MTX group were lower than IL-6 group, but there were no statistically significant differences ( P >0.05). Conclusions: Our data indicated that MTX combined with CTX significantly inhibited IL-6 induced JAK2-STAT3 activation, as well as the induction of P-gp. Inhibition of IL-6-mediated multidrug resistance signaling pathways by the alliance of MTX and CTX may represents a new reversing drug-resistance therapeutic strategy for RA. References: Li HX, Zhao W, Shi Y, et al. Retinoic acid amide inhibits JAK/STAT pathway in lung cancer which leads to apoptosis. Tumour Biol. 2015; 36(11): 8671–8678. Oh HM, Lee SW, Yun BR, et al. Vigna angularis inhibits IL-6-induced cellular signalling and ameliorates collagen-induced arthritis. Rheumatology (Oxford). 2014; 53(1): 56–64. Li R, Cai L, Ren DY, Xie XF, Hu CM, Li J. Therapeutic effect of 7, 3'-dimethoxy hesperetin on adjuvant arthritis in rats through inhibiting JAK2-STAT3 signal pathway. Int Immunopharmacol. 2012; 14(2): 157–163. Yun M, Lee D, Park MN, et al. Cinnamaldehyde derivative (CB-PIC) sensitizes chemo-resistant cancer cells to drug-induced apoptosis via suppression of MDR1 and its upstream STAT3 and AKT signalling. Cell Physiol Biochem. 2015; 35(5): 1821–1830. Disclosure of Interest: None declared